The Usefulness of Elemental Iron for Cereal Flour Fortification: a Sustain Task Force Report. (25th September 2014) - Hurrell, Richard; Bothwell, Thomas; Cook, James D.; Dary, Omar; Davidsson, Lena; Fairweather-Tait, Susan; Hallberg, Leif; Lynch, Sean; Rosado, Jorge; Walter, Tomas; Whittaker, Paul
Abstract : Fortification of cereal flours may be a useful public health strategy to combat iron deficiency. Cereal flours that are used shortly after production (e.g., baking flour) can be fortified with soluble iron compounds, such as ferrous sulfate, whereas the majority of flours stored for longer periods is usually fortified with elemental iron powders to avoid unacceptable sensory changes. Elemental iron powders are less well absorbed than soluble iron compounds and they vary widely in their absorption depending on manufacturing method and physicochemical characteristics. Costs vary with powder type, but elemental iron powders are generally less expensive than ferrous sulfate. This review evaluates the usefulness of the different elemental iron powders based on results from in vitro studies, rat assays, human bioavailability studies, and efficacy studies monitoring iron status in human subjects. It concludes that, at the present time, only electrolytic iron powder can be recommended as an iron fortificant. Because it is only approximately half as well absorbed as ferrous sulfate, it should be added to provide double the amount of iron.